2014
DOI: 10.1111/liv.12618
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for perihilar cholangiocarcinoma: A hospital‐based case–control study

Abstract: Our data showed that DM, heavy smoking, choledocholithiasis and hepatolithiasis were risk factors for pCCA development, implying that pCCA may share some aetiological factors with intrahepatic CCA although it has been classified as extrahepatic CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 27 publications
(35 reference statements)
1
44
0
Order By: Relevance
“…Three studies were conducted in Western countries [10,16,19] of which approximately 97% of participants were white. Other 4 studies were conducted in Asian countries with no demonstrated proportion of race [9,17,18,20]. Three studies were communitybased case-control studies [10,17,19], while the other 4 studies were hospital-based case-control studies [9,16,18,20].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies were conducted in Western countries [10,16,19] of which approximately 97% of participants were white. Other 4 studies were conducted in Asian countries with no demonstrated proportion of race [9,17,18,20]. Three studies were communitybased case-control studies [10,17,19], while the other 4 studies were hospital-based case-control studies [9,16,18,20].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Only one study used hepatic steatosis index for diagnosis of NAFLD [19]. Among the 7 included studies, 4 studies clearly stated that all participants in control groups underwent the same procedure as cases for diagnosis of NAFLD, such as imaging, histopathology examination, or laboratory test for hepatic steatosis index [9,[18][19][20]. Regarding the study quality, four studies were classified as good quality [16,[18][19][20] and the other 3 studies were classified as fair quality [9,10,17] (Table 1 and Additional file 2: Data S5).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations